PENGARUH KEPERCAYAAN DIRI SISWA DALAM MENCAPAI STANDAR KOMPETENSI LULUSAN SMK JURUSAN TATA NIAGA - Hardisem Syabrus (Universitas Tribhuwana Tunggadewi, 2019)
This research aims to determine the extent to which students have confidence in achieving graduate competency standards. The study was conducted by survey method using observation and questionnaires to 126 vocational students at the SMK Commerce in the City of Pekanbaru. The results of this research explained that in general, students’ self-confidence reached “graduated competency standard” at a moderate level (average = 3.57, STDV = .543). Which is there’s only 5 items from competency standards that have high self-confidence with percentage of 56,15%, while there’s 7 items that have moderate self-confidence with percentage of 43,85%. The results showed that the importance of growing students' confidence in achieving overall graduate competency standards, and it is expected that teachers also improve simulations in the learning process especially to improve 7 items in the competency standards so that high student confidence is achieved.